2004
DOI: 10.1073/pnas.0404974101
|View full text |Cite
|
Sign up to set email alerts
|

Activation-induced cytidine deaminase (AID) can target both DNA strands when the DNA is supercoiled

Abstract: The activation-induced cytidine deaminase (AID) is required for somatic hypermutation (SHM) and class-switch recombination of Ig genes. It has been shown that in vitro, AID protein deaminates C in single-stranded DNA or the coding-strand DNA that is being transcribed but not in double-stranded DNA. However, in vivo, both DNA strands are mutated equally during SHM. We show that AID efficiently deaminates C on both DNA strands of a supercoiled plasmid, acting preferentially on SHM hotspot motifs. However, this D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
149
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(157 citation statements)
references
References 28 publications
7
149
1
Order By: Relevance
“…Analysis of the products of SHM in B cells, however, reveals that both DNA strands are mutated (13). Other in vitro studies have shown that AID can deaminate both strands within regions of supercoiled DNA (14) and that the ssDNA-binding replication protein A is required for deamination of SHM targets (15). All of these findings are consistent with the idea that transient formation of ssDNA during transcription facilitates AID action.…”
supporting
confidence: 77%
“…Analysis of the products of SHM in B cells, however, reveals that both DNA strands are mutated (13). Other in vitro studies have shown that AID can deaminate both strands within regions of supercoiled DNA (14) and that the ssDNA-binding replication protein A is required for deamination of SHM targets (15). All of these findings are consistent with the idea that transient formation of ssDNA during transcription facilitates AID action.…”
supporting
confidence: 77%
“…An alternative, but not mutually exclusive, model for generating AID‐accessible ssDNA is based on the formation of denaturation bubbles generated by transcription‐associated negative supercoiling (Shen & Storb, 2004; Shen et al , 2005; Parsa et al , 2012). In regions of very active transcription, topoisomerase‐mediated resolution of the negative supercoiling generated in the wake of RNAPII does not appear to be able to keep pace resulting in overall negative supercoiling upstream of RNAPII (Kouzine et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In regions of very active transcription, topoisomerase‐mediated resolution of the negative supercoiling generated in the wake of RNAPII does not appear to be able to keep pace resulting in overall negative supercoiling upstream of RNAPII (Kouzine et al , 2008). Negative supercoiling creates localised denaturation bubbles (Jeon et al , 2010), which have been shown to provide an ideal substrate for AID on both strands of a plasmid, even in the absence of transcription (Shen & Storb, 2004; Shen et al , 2005). Transcription‐associated negative supercoiling has also been proposed to explain the short patches of AID and bisulphite‐accessible ssDNA observed in the Ig genes of hypermutating Ramos cells and stimulated murine primary B cells (Ronai et al , 2007; Parsa et al , 2012), which are similar to the patches of ssDNA we observe in the diversifying IGVL R of DT40 and, importantly, show are sensitive to the absence of H3.3.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter context, it was reported that AID can target both DNA strands in the context of transcription with Escherichia coli RNA polymerase (28). Another possibility is that differences in chromatin structure or supercoiled DNA in vivo could allow AID to access both strands (29). Finally, it is conceivable that antisense transcription through variable regions and S regions could target AID to both strands (30).…”
mentioning
confidence: 99%